UJI BEBERAPA JENIS POC DAN PUPUK NPK ORGANIK TERHADAP PERTUMBUHAN SERTA PRODUKSI TANAMAN LABU MADU (Cucurbita moschata) - Eko Fakhrorrozi; Fathurrahman (DINAMIKA PERTANIAN, 2023)
This research discusses the interaction of several types of liquid organic fertilizer (LOF) and organic NPK on the growth and production of honey pumpkin (Cucurbita moschata) plants. The research has been carried out on the experimental farm of the Faculty of Agriculture, Riau Islamic University, Jalan Kaharuddin Nasution Air Dingin Village, Bukit Raya District, Pekanbaru City. This research was conducted for 4 months, starting from August to November 2021. This study used a factorial, completely randomized design (CRD) consisting of 2 factors, namely, the first factor was the LOF of giant leucanea leaves, rain tree leaves, and peanut leaves, consisting of 4 levels, namely: 0, 65, 65, and 65 ml/l. The second factor is organic NPK fertilizer, which consists of 4 levels, namely 0, 10, 20, and 30 g/plant. Parameters observed were: stem diameter, flowering age, harvest age, number of fruits per plant, fruit weight per plant, fruit length per fruit, fruit weight per fruit, and fruit sweetness level. The research data were analyzed statistically and continued with the 5% HSD test. The results showed that the treatment of LOF and organic NPK fertilizer had a significant effect on the research parameters. The best treatment was given to peanut leaf LOF and organic NPK at a dose of 30 g/plant. The main effect of LOF in peanut leaves had a significant effect on the research parameters. The best treatment was the provision of peanut leaf LOF. The interaction effect of organic NPK fertilizer had a significant effect on the research parameters.